Konsolidasi Komunal sebagai Mitigasi Konflik Agama di Jawa Timur - Abdul Fatah (Lentera Hukum, 2018)
Indonesia adopts democracy based on the rule of law as it is guaranteed in the constitution. But, the practice of violations of Freedom of Religion and Belief (KBB) still frequently occurs in Indonesia, including in the province of East Java. As a result of intolerance under the ground of religion and belief, social conflict is inevitable. There are several alternatives as a means to establish transitional justice in the aftermath of conflict, such as truth finding, independent and impartial tribunal, mainstreaming collective consciousness on the importance of diversity, and utilization of policy to counter social conflict. Nevertheless, another important aspect is the need of communal consolidation in the aftermath of intolerant practice and social conflict. Thus, communal consolidation which involves interested parties should be seen as an instrument of conflict mitigation under the ground of religion in East Java. Keywords: The Rule of Law, Government, Freedom of Religion and Belief